Interactive teaching materials flif pdf corporate using PBL model in elementary schools - Yetti, Mirna; Reinita, Reinita (Universitas Ahmad Dahlan, 2024)
This research was motivated by the lack of learning resources available in schools and the lack of variety in learning resources. The available learning resources are still in printed form and do not yet use teaching materials that use technology (Digital). This type of research is development research (R&D) using the ADDIE model. The ADDIE model consists of five steps: analysis, design, development, implementation, and evaluation. The subjects used were 22 grade V elementary school students. The data collection techniques used were interviews, validation sheets, questionnaires, and questions. The data obtained was analyzed quantitatively and qualitatively. The results of research on interactive teaching materials obtained a validity level of 85% from the material aspect, 83.33% from the language aspect, and 93.33 from the media aspect,t with a very valid category. Learning using interactive teaching materials is very practical, with the percentage of teacher responses at the research school being 90% and the percentage of student responses at the research school being 84.31%. Then, the effectiveness of interactive teaching materials showed very effective results, with a percentage increase in student learning outcomes of 86.2%. Thus, it can be concluded that interactive teaching materials using the Flip PDF Corporate application in elementary schools have been declared valid, practica,l and effective for use in the learning process.